Wybrane aspekty refakturowania na gruncie ustawy o podatku od towarów i usług - Zając-Wysocka, Justyna (Kwartalnik Prawa Podatkowego, 2015)
The above elaboration, which concerns about the nature of the institution of reinvoice on the basis of the current VAT Act, allows to give some conclusions. Undoubtedly, reinvoice in the present form cannot be identified with a simple reimbursement of the costs of services provided by the taxpayer. The strong argument for the thesis presented hereinabove is Article 8. 2a of the VAT Act, which provides a legal fiction whereby an entity who resells service is treated as its provider. This feature of reinvoice requires the thereof perception in a manner distinct from a simple reimbursement. Assessing the reinvoice in the context of services of a complex nature, it should be noticed that only complex services in whole can be resold. The very nature of a complex service makes impossible using Art. 8.2a for ancillary services. To determine whether it is possible to resell a service in a particular case, it is necessary to analyze the characteristics of a specific group of services in the context of its complexity – this conclusion also concerns the reselling of utilities, supplied in terms of the rental service. As a classic example of resold service can be used services provide by subcontractors, who perform services in their own name, but on behalf of the main contractor. Tax liability from resold services should be defined at general principles – it arises at the time when resold service is supplied. By contrast, when arising of tax liability is associated with the time of preparing the invoice, the while of preparing the reinvoice will be a decisive moment.